Effectiveness of Capital Controls in Selected Emerging Markets in the 2000's - Baba, Chikako (IMF Working Papers; Working Paper ;, 2011)
This paper estimates the effectiveness of capital controls in response to inflow surges in Brazil, Colombia, Korea, and Thailand in the 2000s. Controls are generally associated with a decrease in inflows and a lengthening of maturities, but the relationship is not statistically significant in all cases, and the effects are temporary. Controls are more successful in providing room for monetary policy than dampening currency appreciation pressures. We argue that the macroeconomic impact of capital controls depends on the extensiveness of the policy, the level of capital market development, the support provided by other policies, and the persistence of capital flows.